Influence of organizational culture on knowledge management practices in Inland Revenue Board of Malaysia (IRBM) / Syahida Yaacob ... [et al.] - Yaacob, Syahida; Pati Khan, Mazlina; Abdul Kadir, Irwan Kamaruddin; Masron, Mohd Zairul (Faculty of Information Management, 2022)
Organizational culture distinguishes truly successful businesses from the rest. This paper aims to explore how organizational culture influences knowledge management practices in IRBM. The study identified several characteristics of organizational culture that influence knowledge management practices in IRBM by referring to Denison’s Organizational Culture Model. The study mainly used a qualitative approach by using the semi-structured interview with six (6) individuals to explore their perspectives regarding the influence of organizational culture on KM Practices in IRBM. As a result, the study found that employees were unfamiliar with the term Knowledge Management. Thus, this situation required Human Resources (HR) practicing centralize all HR documents, policies, information, and knowledge and making that vital accessible.